De Estação Experimental de Passo Fundo à Embrapa Trigo : políticas públicas, história e memórias (1937-1974) - Camargo, Elias José (2022)
The Passo Fundo Experimental Station, created in 1937 during the Vargas Era, and Embrapa Trigo, created in 1974 during the military period, were two public institutions created by the Brazilian State with the aim of developing, in particular, wheat genetic research to enable the increase in food production in Brazil. The performance of these institutions is of great importance in the constitution of the history of agriculture in the north-central of the state of Rio Grande do Sul, the region where they were installed. In this sense, this work seeks to analyze, from a historical perspective, the role of the Brazilian State in this modernizing process, having as object of study the Experimental Station of Passo Fundo and, later, Embrapa Trigo, which succeeded the Experimental Station in a process of deepening and conjectural adaptation of agricultural research in Brazil with the advent of the technological modernization of agriculture. Embrapa Trigo became the National Wheat Research Center – CNPT in 1974. The research was developed through bibliographical analysis, legislation and documents constituting these institutions in articulation with the regional and Brazilian political-economic context within the time frame 1937-1974. The work discusses the role of these research institutions as centers that promote extension, diffusion and technological production aimed at agricultural production. In terms of resources, the study also makes use of the orality of actors who participated in these modernizing processes in the productive sector. In general lines, it can be said that this modernization process applied to agriculture in the North of Rio Grande do Sul and in Brazil in general, was largely due to the actions of the Brazilian State through subsidized credit, rural extension and agricultural research developed in the experimental centers. The Passo Fundo Experimental Station as well as Embrapa Trigo played a role in the diffusion of agricultural technology, becoming indispensable instruments in the process of modernizing capitalist agriculture. At the same time, it is clear that a large part of Brazilian farmers were excluded from such policies.